The effect of health gate sterilizer use on work motivation during post-COVID-19 pandemic: an analysis of educational staff - Sandey Tantra Paramitha; Komarudin Komarudin; Mustika Fitri; Muhammad Gilang Ramadhan (AOSIS, 2022)
This study investigates the use of a health gate sterilizer on its impact on the work motivation of education personnel during the post-COVID-19 pandemic. The research method used is an experiment with a pre-test/post-test group design. This research was carried out for 8 weeks on 120 education staff at an educational institution. Education personnel was chosen because of their importance to the education sector in Indonesia after the COVID-19 pandemic was very disrupted. The treatment given is the use of a health gate sterilizer for educational staff to feel safe and comfortable so that they are expected to be motivated in their work. The results showed that there was a significant and positive effect of the use of a health gate sterilizer on the work motivation of educational staff in educational institutions. From this research, it can be concluded that the use of a health gate sterilizer must continue to be used in order to have a positive impact on motivating one's work because it does provide a sense of security and comfort from the COVID- 19 virus.